Impact of Time-Restricted Feeding to Late Night on Adaptation to a 6 h Phase Advance of the Light-Dark Cycle in Mice - Ren, Baoyin; Ma, Changxiao; Chen, Lihong; FitzGerald, Garret A.; Yang, Guangrui (Frontiers in Physiology, 2021)
In modern society, more and more people suffer from circadian disruption, which in turn affects health. But until now, there are no widely accepted therapies for circadian disorders. Rhythmic feeding behavior is one of the most potent non-photic zeitgebers, thus it has been suggested that it was important to eat during specific periods of time (time-restricted feeding, TRF) so that feeding is aligned with environmental cues under normal light/dark conditions. Here, we challenged mice with a 6-hour advanced jet lag, combined with various approaches to TRF, and found that food restricted to the second half of the nights after jet lag facilitated adaptation. This coincided with improved resilience to sepsis. These results raise the possibility of reducing the adverse responses to jet lag by subsequent timing of food intake.